Developments on Synthesis and Applications of Sulfobetaine Derivatives: A Brief Review - Eva Oktavia Ningrum; Eva Lestiana Pratiwi; Isyarah Labbaika Shaffitri; Suprapto Suprapto; Mentari Rachmatika Mukti; Ely Agustiani; Niniek Fajar Puspita; Achmad Dwitama Karisma (Indonesian Journal of Chemistry, 2021)
Zwitterionic polymers are material families characterized by high dipole moment and highly charged groups. Zwitterionic materials simultaneously possess an equimolar number of cationic and anionic moieties, maintaining overall electroneutrality and high hydrophilicity. Zwitterionic is categorized into three groups: phosphobetaine, carboxybetaine, and sulfobetaine that could form dense and stable hydration shells through the strong ion-dipole interaction among water molecules and zwitterions. As a result of their remarkable hydration capability, low interfacial energy, and marvelous antifouling capacities, these materials have been applied as adsorbing agents, biomedical applications, electronics, hydrogels, and antifouling for membrane separation and marine coatings. This review is focused on polysulfobetaine, which contains sulfonate as a negatively charged group, and quaternary ammonium as a positively charged group. Polysulfobetaine is the most promising one to be applied in the industry since it is commercially available and its monomers are easily prepared. The comparisons of several polysulfobetaine derivatives as antimicrobial, antifouling, surfactant and detergents, biomedical and electronic application, surface modification, and smart hydrogel are presented in this review.